(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The paper is focused on the analysis of the characteristics that medical services dedicated to the protection of gender identity, in childhood and developmental age, must present according to international scientific guidelines, medical literature, international normative sources and national discipline, read in the light of constitutional jurisprudence and the opinions of the Italian National Bioethics Committee. The analysis highlights the importance of specialized services and, for those who require them, personalized care pathways, which can ensure the effective exercise of the rights to self-determination and health of children with gender incongruence and can also be decisive for the enjoyment of other fundamental rights (to education, sports etc.) and, ultimately, for the full development of their personality. Critical issues that may limit the enjoyment of such services in the Italian territory and that deserve to be overcome are therefore pointed out.